The Correlation Of Parity And Nutritional Status With The Incident Of Hyperemesis Gravidarum In The Pratama Dendang Tirta Clinic, Stabat District, Langkat District, 2023 - Yulianda, Endang; Eva Ratna Dewi; Romida, Alniar; Agussamad, Indra (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2023)
Hyperemesis gravidarum occurs more frequently in multiple pregnancies and hydatidiform moles than in pregnancies without other complications. Hyperemesis gravidarum is a symptom of excessive vomiting in pregnant women which causes weight loss (more than 5% of initial body weight), dehydration, ketosis, and abnormal electrolyte levels. This study aims to analyze the relationship between parity and nutritional status with the incidence of hyperemesis gravidarum at the Dendang Tirta Pratama Clinic, Stabat District, Langkat Regency in 2023. The type of research used in the research is a cross-sectional design. The research sample was 35 pregnant women at the Pratama Dendang Tirta Clinic, Stabat District, Langkat Regency using total sampling techniques. Data were analyzed by conducting a Chi-square analysis test. The results of the research were statistical tests using the Chi-Square test with the test results used being the Fisher Excat Test with a value of p = 0.012. Thus the p value < α 5%, 0.012 < 0.05. This researcher stated that there was a relationship between parity and nutritional status with the incidence of hyperemesis gravidarum. It is recommended that mothers always seek information about hyperemesis gravidarum and risk factors for hyperemesis gravidarum, so that during pregnancy mothers can consume nutritious food for the health of their fetus during pregnancy.